A paradoxical role of reactive oxygen species in cancer signaling pathway: Physiology and pathology. (January 2021) - Ramalingam, Vaikundamoorthy; Rajaram, Rajendran
Graphical abstract: Highlights: ROS are free radicals derived from both intracellular and extracellular sources. ROS are generated by O2 utilization, partial O2 degradation, & cellular breakdown. ROS play an active role in initiation and regulation of cancer signaling pathways. The low and high levels of ROS control the various signaling pathways. ROS is a double-edged sword in regulating cellular homeostasis and carcinogenesis. Abstract: Reactive oxygen species (ROS) are generally recognized as major products in the cells that are produced during oxygen utilization, cellular breakdown, and the incomplete degradation of oxygen molecules. Deep research over the last two decades shows that ROS is the key factor for the initiation and regulation of cancer signaling pathways. The unique charisma of cancer cells is their ability to produce an elevated amount of oxidative stress and their requirement for an antioxidant defence system that differentiates the cancer cells from the normal cells. The low and high level of ROS controls the various signaling pathways associated with tumorigenesis, oncogenesis, angiogenesis, autophagy, lipid, glucose metabolism, etc. The elevated ROS level is a well-known hallmark for various cancer resulting in apoptosis by regulating pro-tumorigenic and anti-tumorigenic signaling pathways. In the meantime, the reduced ROS level contributes to cell survival, invasion, metastasis, oncogenesis, etc. The significant role of this double-edged sword ROS in cellular homeostasis, as well as carcinogenesis, will be discussed in this review. Moreover, the present review deals with the various intracellular and extracellular sources of ROS generation, the significant role of ROS, and provides a brief overview of the ROS signaling pathway in cancer.